(untitled) (AL-FIKRAH: Jurnal Kajian Islam, 2025)
This study aims to analyze the view of the fiqh rule al-ḍarar yuzāl (harm must be eliminated) in the vasectomy procedure as a method of contraception that aims to optimize the health protection of wives. This rule is an important foundation in Islamic law to provide solutions to health problems that can endanger life. The research method used is descriptive qualitative research that focuses on literature studies using a normative approach that examines the relevance of the al-ḍarar yuzāl rule on medical aspects and Islamic law in vasectomy procedures. The results show that vasectomy cannot be justified in the application of the al-ḍarar yuzāl rule. This action is permanent and eliminates the reproductive function intentionally, thus contradicting the principles of Islamic law. Although there is a medical risk of recurrent pregnancy, there are other contraceptive methods available that are milder and reversible. Therefore, the law of vasectomy remains haram and should not be performed, both in normal and emergency conditions. The implications of this study are expected to be a reference in the preparation of contemporary fiqh fatwas on contraception, as well as a guide for doctors and Muslim couples in making medical decisions that are in accordance with Syariat.